Sociodemographic and cultural factors are related to singlehood rates: A multilevel analysis across 59 countries from the World Values Survey - Marta Kowal; Katarzyna Adamczyk (PLoS ONE, 2025)
Singlehood, which refers to remaining without a lifetime partner, has become an increasingly common phenomenon. However, there is still limited understanding of the individual-level sociodemographic and country-level cultural factors that predict one’s singlehood status. We addressed this question by utilizing data from the World Values Survey, which included responses from 71,169 individuals across 59 countries. Through multilevel modeling, we discovered that several factors increase the likelihood of being single. These factors include being younger, being male, residing in a larger town, having a higher level of education, having a lower income, being unemployed, and living in countries characterized by higher individualism and lower flexibility. Additionally, the likelihood of being single varied according to country-level individualism and flexibility, interacting with various individual-level factors. These findings suggest that the significance of individual sociodemographic characteristics on the prevalence of single individuals depends on country-level traits related to individualism-collectivism and flexibility-monumentalism.